Adoption of Soil Fertility Management Technologies in Malawi: Impact of Drought Exposure - Samson P. Katengeza; Stein T. Holden; Monica Fisher (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
Soil fertility management (SFM) technologies may potentially protect against climate risks, reduce nutrient depletion and enhance food security. In this paper, we study impact of drought exposure on adoption and adoption intensity of SFM technologies, specifically, focusing on maize-legume intercropping and organic manure. The paper uses four-round panel data collected from six districts in Malawi over a period of nine years and we use correlated random effects models with a control function approach for data analysis. Results show an increase in adoption rates from 33% in 2006 to 76% in 2015 for maize-legume intercropping and from 30% (2006) to 53% (2015)for organic manure. Regression results reveal that exposure to early and late dry spells increases the likelihood of adoption and adoption intensity of maize-legume intercropping with late droughts also having a positive impact on adoption and adoption intensity of organic manure. We also find positive effects of fertilizer use intensity and fertilizer price on adoption and adoption intensity of both intercropping and organic manure.
Keywords: Q12; Q16; Q54; Q56; 330; Soil fertility management; maize-legume intercropping; organic manure; adoption; drought impacts; Malawi